Alle soglie della villa fiorentina: l’architettura delle dimore rurali nel Trecento - Frati, Marco (Opus Incertum, 2016)
This contribution attempts to quantitatively and qualitatively analyse the phenomenon of the extra-urban residences in theregion around Florence, which was a precursor of the later, much more widely known and formally recognised phenomenon of therenaissance villa. Proceeding backwards in time, the first step will be that of evaluating the persistence of the structures of medievalresidences during the first modern era (15th-16th centuries); after which an attempt will be made to make a comprehensive overviewof the phenomenon through the analysis of historical documents and regional samples which may provide statistical informationand quantitative projections. An effort will be made as well to outline the innovative elements that characterise Florentine countryresidences, extricating meaning from the terminological difficulties created by the documentation and by the various typologiesproposed by historiography, drawing from specific cases that can be examined and attempting to determine their compositive andsymbolic worth.